Comparison between polyphenol contents and antioxidant activities of different parts of Capparis spinosa L - Arrar, Lekhmici; Benzidane, Nadia; Krache, Imane; Charef, Noureddine; Khennouf, Seddik; Baghiani, Abderrahmane (Pharmacognosy Communications)
Introduction: Capparis spinosa L., Capparidaceae is a shrub growing widely in Algeria. Aqueous and methanolic extracts of five parts of the plant were studied for their polyphenol and flavonoid contents. These extracts were also evaluated for their antioxidant and anti-lipid peroxidation effects. Material and Methods: determination of polyphenols and flavonoids was carried out using colorimetric methods. Antioxidant and anti-lipid peroxidation of extracts were performed using the established DPPH and beta carotene/linoleic acid tests. Results: The methanolic extracts contained higher total polyphenols and flavonoids than the aqueous extracts. The leaves and flowers were rich in polyphenols and/or flavonoids whilst the roots were relatively poor in these components. Furthermore, all extracts had anti-lipid peroxidation and antioxidant effects with higher levels in the flowers and the leaves (I% = 82.78 ± 2.64% and 80.94 ± 1.57%, respectively). Seeds have an importanteffect (I% = 64.02%) followed by fruits then roots (I% = 40.62% and 21.24%, respectively). Conclusion: These results demonstrated the antioxidant and anti-lipid peroxidation of all parts of Capparis spinosa and give a comparative data on the extracts of different parts that can be used in the diseases where inhibition of oxidative stress is required.
Keywords: Capparis spinosa; antioxidant; methanolic extract; aqueous extract; lipid peroxidation